Rapid genotyping of the genetic variants of organic anion transporter 1 (OAT1), R50H, R23W, R454Q, and 505C>T, by pyrosequencing method - Shin, Ho Jung; Lee, Choong-Hee; Lee, Sang Seop; Shin, Jae-Gook; Song, Im-Sook (Journal of pharmaceutical investigation, 2012)
The organic anion transporter 1 (OAT1 encoded by SLC22A6 ) plays a critical role in renal elimination of various endogenous anions and clinically important anionic drugs in humans. In the present study, we developed a rapid genotyping method for use in the evaluation of the clinical significance and ethnic distribution of three functional OAT1 variants [R50H (149G>A; rs11568626), R293W (877C>T; rs45607933), R454Q (1361G>A; rs11568634)] and of a high-frequency OAT1 SNP, 505C>T (rs10897312). In a validation experiment using 50 Korean subjects, genotype results obtained using our duplex pyrosequencing method yielded 100% concordance with those obtained using direct sequencing. When our assay was used to compared OAT1 genotypes among five ethnic groups: Korean, Chinese, Vietnamese, Caucasian (100 subjects each) and African-American (83 subjects), the observed frequencies of the 505C>T SNP in the Korean (27%), Chinese (24%), Caucasian (10%), and African-American (35.5%) populations were similar to those reported in the HapMap database. Additionally, the allele frequencies of R50H SNP were 1%, 2%, and 6% in Chinese, Caucasian, and African-American, respectively. The R293W and R454Q variants were not detected in any of the study populations because of the low frequencies of these SNPs. These results demonstrate the utility of our duplex pyrosequencing assay for rapid, accurate, and cost-effective genotyping of the R50H, R293W, R454Q, and 505C>T variants of OAT1.